2022
DOI: 10.1136/annrheumdis-2021-221866
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and interferon gamma response drive the phenotype of neutrophils in the inflamed joint

Abstract: ObjectiveNeutrophils are typically the most abundant leucocyte in arthritic synovial fluid. We sought to understand changes that occur in neutrophils as they migrate from blood to joint.MethodsWe performed RNA sequencing of neutrophils from healthy human blood, arthritic blood and arthritic synovial fluid, comparing transcriptional signatures with those from murine K/BxN serum transfer arthritis. We employed mass cytometry to quantify protein expression and sought to reproduce the synovial fluid phenotype ex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In murine neutrophils, the combination of GM-CSF and LPS led to a stronger increase in expression of CD14, CD69, IL-4R and CD40 compared to GM-CSF and IFN-γ. The reverse was true for PD-L1, which is driven substantially by IFN-γ signaling (8). In mice, IFN-γ stimulation reduced CD69 expression, while LPS increased it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine neutrophils, the combination of GM-CSF and LPS led to a stronger increase in expression of CD14, CD69, IL-4R and CD40 compared to GM-CSF and IFN-γ. The reverse was true for PD-L1, which is driven substantially by IFN-γ signaling (8). In mice, IFN-γ stimulation reduced CD69 expression, while LPS increased it.…”
Section: Resultsmentioning
confidence: 99%
“…For example, human neutrophils are highly abundant in defensins, yet their murine orthologs are expressed in gut epithelial cells, not in neutrophils. Furthermore, neutrophils display high phenotypic and functional heterogeneity as a function of organ, maturation and inflammatory condition (6)(7)(8)(9), but whether a core inflammation program consisting of genes that become induced across a range of inflammatory conditions exists, is not known. It is thus unclear how similarities and differences between human and mouse transcriptomes should be interpreted, particularly in the context of different inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). In addition, neutrophil migration into inflamed tissues, such as the inflamed joint in patients with rheumatoid arthritis, is considered a strong driver of changes in gene and protein expression, creating further complexity in terms of neutrophil heterogeneity between blood and tissues 35 .…”
Section: Neutrophil Biologymentioning
confidence: 99%
“…Their activity is strictly influenced by T cells, indeed it has been demonstrated that while circulating neutrophils do not significantly differ from healthy donors, those infiltrating the SF display an IFN-γ signature at transcriptomic level. SF neutrophils have also phenotypic abnormalities, such as CXCR1 downregulation and upregulation of CD11c, PD-L1, ICAM-1, HLA-DR [32 ▪ ,18]. An elevated percentage of CXCR4 + neutrophils was observed in SF, allowing these cells to respond to CXCL12/SDF-1 and to be retained in the inflamed tissue [32 ▪ ,18].…”
Section: T Cells and Innate Immunitymentioning
confidence: 99%
“…SF neutrophils have also phenotypic abnormalities, such as CXCR1 downregulation and upregulation of CD11c, PD-L1, ICAM-1, HLA-DR [32 ▪ ,18]. An elevated percentage of CXCR4 + neutrophils was observed in SF, allowing these cells to respond to CXCL12/SDF-1 and to be retained in the inflamed tissue [32 ▪ ,18]. Finally, SF neutrophils display an aged phenotype (CD16high, CD62low), differently from those in the blood that instead are primarily CD16high CD62Lhigh [33].…”
Section: T Cells and Innate Immunitymentioning
confidence: 99%